PENGARUH TABUNGAN, DEPOSITO, DAN GIROTERHADAP RENTABILITAS PERUSAHAAN PERBANKAN Studi Kasus Bank Mandiri Yang Terdaftar di Bursa Efek Indonesia Periode 2012 - 2014 - Citra Ayu Putri Pratiwi; Harsi Romli; Iwan Efriandy (Universitas Indo Global Mandiri)
The purpose of this study was to determine the effect on the profitability of savings PT.Bank Mandiri Tbk, the effect on the profitability of deposits PT.Bank Mandiri Tbk, giro effect on corporate profitability partially, and the effect of savings, deposit and current accounts toward profitability PT.Bank Mandiri, Tbk simultaneously. The method used in this research is quantitative research methods, data is expressed in the form of numbers. The data used in this research is secondary data such as financial statements, namely the balance of PT.Bank Mandiri Tbk years 2012-2014. The study concluded that portially there is a significant and positive impact on the profability of savings, meaning that f the savings increase, will increase the profitability of PT.Bank Mandiri, Tbk in carrying out the duties and functions as the manager of banking funds. Partially also a positive and significant impact on the profitability of the deposit, it implies that if there is an increase in deposits will increase the profitability of PT.Bank Mandiri Tbk, partially also a positive and significant influence between giro towards profitability, it implies that if there is an increase in demand that will increase the profitability of PT.Bank Mandiri Tbk, and jointly or simultaneously a positive and significant influence between savings, deposits, and curret accounts of the profitability of the company, this means that if there is an increase in savings, deposits, and current accounts will increase the profitability of PT.Bank Mandiri Tbk.